2015
DOI: 10.1177/2325967115602255
|View full text |Cite
|
Sign up to set email alerts
|

Distal Insertions of the Biceps Femoris

Abstract: Background:Avulsion of the biceps femoris from the fibula and proximal tibia is encountered in clinical practice. While the anatomy of the primary posterolateral corner structures has been qualitatively and quantitatively described, a quantitative analysis regarding the insertions of the biceps femoris on the fibula and proximal tibia is lacking.Purpose:To quantitatively assess the insertions of the biceps femoris, fibular collateral ligament (FCL), and anterolateral ligament (ALL) on the fibula and proximal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 23 publications
3
36
0
4
Order By: Relevance
“… 16 , 31 The short head component, originating from the linea aspera on the posterior aspect of the femoral diaphysis, converges and coalesces with the tendon of the long head of the biceps femoris (originating from the ischial tuberosity) in the posterolateral aspect of the distal half of the thigh. 6 , 31 In their study of 30 cadaveric knees, Terry and LaPrade 31 provided detailed anatomic descriptions of the tendinous insertions of the distal biceps femoris. The authors reported that the tendinous insertion of the long head includes a direct arm inserting on the posterolateral aspect of the proximal fibula and an anterior arm inserting along the lateral edge of the proximal fibula, lateral to the fibular collateral ligament (FCL) and distally along the anterior aponeurosis in the anterior compartment of the leg.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 31 The short head component, originating from the linea aspera on the posterior aspect of the femoral diaphysis, converges and coalesces with the tendon of the long head of the biceps femoris (originating from the ischial tuberosity) in the posterolateral aspect of the distal half of the thigh. 6 , 31 In their study of 30 cadaveric knees, Terry and LaPrade 31 provided detailed anatomic descriptions of the tendinous insertions of the distal biceps femoris. The authors reported that the tendinous insertion of the long head includes a direct arm inserting on the posterolateral aspect of the proximal fibula and an anterior arm inserting along the lateral edge of the proximal fibula, lateral to the fibular collateral ligament (FCL) and distally along the anterior aponeurosis in the anterior compartment of the leg.…”
Section: Discussionmentioning
confidence: 99%
“…35 At the tibia, the ALL has an average attachment area of 53.0 to 64.9 mm 2 and attaches an average of 24.7 mm posterior to the center of Gerdy's tubercle and 26.1 mm proximal to the anterior margin of the fibular head. 8,31 The tibial insertion site of the ALL can be found an average of 9.5 mm distal to the joint line and just proximal to the tibial insertion of the biceps femoris. 8,31 BIOMECHANICS Several studies have tested the biomechanical properties of the ALL, with a mean ultimate load to failure measured between 50 and 205 N, a mean stiffness of 20 to 42 N/mm, and a mean ultimate strain of 36%.…”
Section: Anatomymentioning
confidence: 99%
“…A quantitative analysis of distal insertions of the biceps femoris in 2015 identified tibial, distal fibular, medial fibular and proximal fibular footprints as consistent components of the insertion of the biceps femoris. 12 While snapping biceps femoris syndrome is a recognised entity in the literature, it remains an uncommon cause of lateral knee pain with only few case reports and small series published, leaving treating clinicians with little evidence to guide their management. [4][5][6][7][8][9][10][13][14][15][16][17] Most, however, agree on the need for surgical intervention once all non-operative measures have failed to relieve the painful symptomatic snapping.…”
Section: Discussionmentioning
confidence: 99%